THE ANALYTICAL HIERARCHY PROCESS (AHP) ON PURCHASE EVALUATION OF LOW END SMARTPHONE IN MANADO (CASE STUDY : OPPO, ASUS AND ADVAN) - Berhimpon, Gabriella .; Pangemanan, Sifrid S.; Rumokoy, Farlane S. (Universitas Sam Ratulangi, 2018)
Abstract: Smartphones is a sophisticated mobile phones that resemble computers to meet human needs as a communications tool. Consumer purchasing decisions are a process that involves individuals or groups in choosing, purchasing, using or disposing of products, services or experiences to meet their needs. In understanding decision making we will know how consumers make a decision from searching to buy products or services and also we can know the factors that influence decision making. This research uses kuanitatif method to measure data. The method used is Analytical Hierarchy Process method. The AHP method for rating alternative decisions and selecting the best multiple criteria is given, allowing users to assess the relative weights of some criteria given intuitively. Customer will choose Oppo as the most preferred low end smartphone in Manado compared to the other alternatives. The result shows people want to choose the best low end smartphone, they prefer to choose Oppo smartphone among the other alternatives. User interface is the most important criteria for the consumer. The user interface of the low end smartphone much important as the criteria in purchase evaluation because every consumer need their low end smartphone to be able to interact directly.Keywords : customer decision making, analytical hierarchy process